Callus induction and plant regeneration from immature embryos of Brachypodium distachyon with different chromosome numbers - R. Hammami; A. Cuadrado; E. Friero; N. Jouve; C. Soler; J. M. González (Biologia Plantarum, 2011)
The paper reports the in vitro cultivation of two commercial lines and 23 wild populations (with 10, 20 and 30 chromosomes) of Brachypodium distachyon. Callus induction was assayed on Murashige and Skoog medium containing 1 mg dm-3 2,4-dichlorophenoxyacetic acid (2,4-D) with 30 g dm-3 of sucrose (MSs) or maltose (MSm). No significant differences were seen between the two media with respect to callus induction. Calli were transferred to MSm medium without 2,4-D but containing 0.1 mg dm-3 of 6-benzylaminopurine for plant regeneration. The plant regeneration response was very variable depending on the original induction medium, although no overall preference for one or the other medium was seen. The three main culture stages (callus induction, plant regeneration, and green plantlets formation) are probably differently controlled in the plants with different chromosome numbers. This supports the idea that the three cytotypes of Brachypodium cultured actually belong to different species.